Simple. (Problem 7 7 )

Algebra Level pending

( 2 x ) ! = ( x + 1 ) ! (2x)! = (x + 1)!

Find x x where x 0 x \neq 0

Tip: If you want to, you can remove the ! ! sign.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Yajat Shamji
Jul 12, 2020

( 2 x ) ! = ( x + 1 ) ! (2x)! = (x + 1)!

Remove the factorial sign:

2 x = x + 1 2x = x + 1

2 x x = 1 2x - x = 1

x = 1 x = \fbox{1}

Your answer is correct but the method is wrong because of 2 × x ! ( 2 x ) ! 2 \times x! \ne (2x)!

Mahdi Raza - 11 months ago

Log in to reply

( 2 × x ) ! = ( 2 x ) ! (2 \times x)! = (2x)!

Yajat Shamji - 11 months ago

Log in to reply

Still incorrect, if x = 3

3 ! × 2 = 12 6 ! 3! \times 2 = 12 \ne 6!

Mahdi Raza - 11 months ago

Log in to reply

@Mahdi Raza No:

( 2 × 3 ) ! = 6 ! = 720 (2 \times 3)! = 6! = 720

Yajat Shamji - 11 months ago

Log in to reply

@Yajat Shamji What you are saying isn't wrong! But your solution is wrong. In the problem, you have written 2 × x ! 2 \times x! but in the solution, you write it as ( 2 x ) ! (2x)! . And i am saying that the two aren't equal, the answer is same but it isn't applicable for any x x

Mahdi Raza - 11 months ago

Log in to reply

@Mahdi Raza Look above now. Happy?

Yajat Shamji - 11 months ago

Log in to reply

@Yajat Shamji But if you have parentheses, x=0 is a valid answer.

Ved Pradhan - 11 months ago

Log in to reply

@Ved Pradhan Oh yes, the question changes the answer, and now they are 1 and 0, never mind. I don't want to bang my head into the wall. I still repeat it!:

2 × ( x ) ! ( 2 x ) ! 2 \times (x)! \ne (2x)!

Mahdi Raza - 11 months ago

Log in to reply

@Mahdi Raza Look above again.

Yajat Shamji - 11 months ago

Log in to reply

@Yajat Shamji Great! I would still suggest adding brackets 2 x ! ( 2 x ) ! 2x! \implies (2x)! and ask what is the sum of values of x x . The answer will still remain 1 + 0 = 1 1 + 0 = 1 . Thanks for adding it!

Mahdi Raza - 11 months ago

Log in to reply

@Mahdi Raza Look now. But I am not asking for the sum of values of x x .

Yajat Shamji - 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...